Raymond Swing papers - Swing, Raymond, 1887-1968.
Primarily scripts of Swing's radio broadcasts including those presented on the Blue Network; the British Broadcasting Corporation; Mutual Broadcasting System; radio stations WMAL (Washington, D.C.), WOL (Washington, D.C.), and WOR (New York, N.Y.); and Voice of America. Scripts reflect Swing's analysis and interpretation of world news during the period between 1935 and 1964. Includes correspondence, lectures, addresses, articles written (1941-1943) for the London Sunday Express, poetry, and plays by Swing. Subjects include antinuclear bomb efforts, blackballing of Carl T. Rowan by the Cosmos Club, Chinese Communists (Zhongguo gong chan dang), disarmament in the 1960s, the Gung Ho unit in the Pacific theater during World War II, a Jewish homeland in Palestine, military leadership, and world government. Correspondents include Evans Fordyce Carlson, James Bryant Conant, Albert Einstein, Edward R. Murrow, Drew Pearson, Dean Rusk, Arthur M. Schlesinger, Adlai E. Stevenson, and Harry S. Truman.
Journalist and radio commentator. Full name: Raymond Gram Swing.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carlson, Evans Fordyce, -- 1896-1947 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Murrow, Edward R. -- Correspondence; Pearson, Drew, -- 1897-1969 -- Correspondence; Rowan, Carl T. -- 1925-2000.; Rusk, Dean, -- 1909-1994 -- Correspondence; Schlesinger, Arthur M. -- 1888-1965 -- Correspondence; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Blue Network Company; British Broadcasting Corporation; Cosmos Club (Washington, D.C.); Mutual Broadcasting System; Voice of America (Organization); WMAL (Radio station : Washington, D.C.); WOL (Radio station : Washington, D.C.); WOR (Radio station : New York, N.Y.); Zhongguo gong chan dang; Sunday express, London; Antinuclear movement; Disarmament; Foreign news; International organization; Jews -- Palestine; Radio programs; Radio scripts; World War, 1939-1945 -- Pacific Ocean; Palestine -- History; Journalists; Radio journalists